Neurological adverse events associated with baclofen: A disproportionality analysis based on FDA Adverse Event Reporting System - Ni Zhang; Tingting Jiang; Yanping Li; Pei Guo; Yumeng Liu; Yu Zhang; Yao Liu (SAGE Open Medicine)
Purpose: Baclofen is a muscle relaxant that could carry the risk for neurological adverse events (nAEs). We aim to analyze the nAE profile of frequently used baclofen for its clinical application. Methods: Our research is a disproportional analysis based on the FDA Adverse Event Reporting System (FAERS) database. We obtained adverse event reports of baclofen from January 2004 to June 2023 from the FAERS database. Reporting odds ratio (ROR) and Bayesian confidence propagation neural network (BCPNN) were performed to find nAE associated with baclofen. Results: We extracted a total of 9305 nAE cases with baclofen as the primary suspect. The patients were mostly under 18 years old (45.49%), with markedly more males (43.72%) than females (36.52%). In all, 7275 (78.18%) reports were from the United States. There were 2023 of 9305 (21.74%) reports that occurred serious adverse events (SAE). The median onset time of reports with baclofen-related nAE was 10 days (interquartile range (IQR) 1–112). Intrathecal injection (75.78%) was more than oral (23.06%). We detected 119 significant signals, among which the higher frequencies were somnolence (ROR: 4.69, 95% CI (4.37, 5.03); IC: 2.17, IC025 (2.06)), tremor (ROR: 2.76, 95% CI (2.50, 3.04); IC: 1.43, IC025 (1.29)), lethargy (ROR: 6.37, 95% CI (5.71, 7.10); IC: 2.61, IC025 (2.45)), status epilepticus (ROR: 8.71, 95% CI (7.07, 10.73); IC: 2.98, IC025 (2.69)), generalized tonic-clonic seizure (ROR: 3.17, 95% CI (2.54,3.95); IC: 1.62, IC025 (1.30)], and cerebrospinal fluid leakage (ROR: 229.56, 95% CI (197.76, 266.47); IC: 6.61, IC025 (6.43)]. Unexpected significant nAE might also occur, such as intracranial hypotension (ROR: 428.52, 95% CI (355.18, 517.00); IC: 6.75, IC025 (6.56)], cognitive disorder (ROR: 2.65, 95% CI (2.21, 3.19); IC: 1.38, IC025 (1.11)], anterograde amnesia (ROR: 7.35, 95% CI (2.74, 19.72); IC: 1.69, IC025 (0.90)], metabolic encephalopathy (ROR: 14.77, 95% CI (10.40, 21.00); IC: 3.55, IC025 (2.93)], and myoclonus (ROR: 5.98, 95% CI (4.70, 7.59); IC: 2.46, IC025 (2.13)]. Conclusion: Given the wide use of baclofen, clinicians should be well-informed about important potential nAE. Although disproportional analysis is a refinement approach, it is still necessary to be vigilant about the nAE of baclofen. It is extremely crucial to early monitoring, especially in minors and the initial stage following the commencement of use.